2008
DOI: 10.1016/j.jacc.2008.03.052
|View full text |Cite
|
Sign up to set email alerts
|

Exaggerated Blood Pressure Response to Exercise Is Associated With Augmented Rise of Angiotensin II During Exercise

Abstract: An exaggerated BP response to exercise was associated with augmented rise of Ang II during exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
2
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(80 citation statements)
references
References 16 publications
6
70
2
2
Order By: Relevance
“…Angiotensin also mediates negative cardiovascular effects through the signaling pathways of reactive oxygen species, which amplifies oxidative stress provoked by other agents 33 and has been linked to increases in exercise BP. 34 According to previous work [35][36][37][38] showing the stronger predictive value of WC for incident HT, our results indicate that WC seems to be more closely associated with BP indices than any other obesity indices, such as BMI (Table 3). Such a conclusion is also consistent with findings from our previous longitudinal study, which indicated that maintaining low levels of visceral adiposity and high levels of CRF were both important targets for the maintenance of a healthy cardiometabolic risk profile (including BP) in apparently healthy individuals.…”
Section: Discussionsupporting
confidence: 71%
“…Angiotensin also mediates negative cardiovascular effects through the signaling pathways of reactive oxygen species, which amplifies oxidative stress provoked by other agents 33 and has been linked to increases in exercise BP. 34 According to previous work [35][36][37][38] showing the stronger predictive value of WC for incident HT, our results indicate that WC seems to be more closely associated with BP indices than any other obesity indices, such as BMI (Table 3). Such a conclusion is also consistent with findings from our previous longitudinal study, which indicated that maintaining low levels of visceral adiposity and high levels of CRF were both important targets for the maintenance of a healthy cardiometabolic risk profile (including BP) in apparently healthy individuals.…”
Section: Discussionsupporting
confidence: 71%
“…Although studies have demonstrated that exercise BP at the brachial level is an important marker of left ventricular hypertrophy [4,5], we also failed to find an association between an EBPR to exercise and left ventricular remodelling or diastolic dysfunction in our previous study [15]. Accordingly, the impact of EBPR to exercise on left ventricular function tends to be inconsistent.…”
Section: Central Haemodynamics and Exercise Blood Pressurecontrasting
confidence: 77%
“…Each individual provided written informed consent to the protocol approved by our institutional review board. Of the 141 individuals, 19 men and 43 women met the definition of an EBPR to exercise defined as a difference between peak and baseline SBP at least 60 mmHg in men and at least 50 mmHg in women during exercise testing [15]. After the exercise test, two individuals (one man, one woman) with a positive exercise echocardiogram for inducible ischemia and one individual with insufficient quality of the recorded central haemodynamics after exercise were additionally excluded.…”
Section: Study Participantsmentioning
confidence: 99%
“…The RAS, one of the main controllers of systemic blood pressure, can contribute to systemic hypertension in humans by exaggerating vasopressor responses to drugs [30], nutrients [31], or exercise [32]. One study, using 3 days of water deprivation in pregnant rats, reported increments in fetal plasma sodium concentration and osmolality in association with increments in fetal liver angiotensinogen mRNA and plasma angiotensin I and angiotensin II levels [33•].…”
Section: Prenatal Exposure To Maternal Water Deprivation and The Renimentioning
confidence: 99%